Blaze [videorecording (DVD)] - Barton, Del Kathryn; Amweero, Huna; Savage, Julia; Baker, Simon, 1969-; McDonald, Will; Lawson, Josh, 1981-; Stone, Yael; Hampson, Sofia (Gravitas Ventures, 2023)
Blaze is the sole witness to a shocking crime. Making sense of what she saw, she unleashes the wrath of her imaginary dragon.